Effects of Electromagnetic Waves Emitted by Mobile Phones on Germination, Root Growth, and Root Tip Cell Mitotic Division of Lens culinaris Medik - Akbal, Ayhan; Kiran, Yasar; Sahin, Ahmet; Turgut-Balik, Dilek; Balik, Hasan H. (Hard, 2012)
In this study, the effects of electromagnetic waves emitted from mobile phones operating at 1800 MHz were investigated on germination, root growth and mitotic division of root tips of Lens culinaris Medik. Seeds were split into three groups. The first group was exposed to a mobile phone electromagnetic field for 48 hours at the state of dormancy, and the second group was exposed to the same electromagnetic field at the state of division. The third group, the control group, was not exposed to an electromagnetic field beyond the natural background. The results obtained in the study indicate that electromagnetic waves emitted from mobile phones affect seeds in the state of dormancy more than the state of germination. Germination rate was not affected under the specified exposure conditions, but root growth decreased due to a possible effect of oxidative stress in the state of dormant seeds. There was also a noticeable increment in the c-mitosis rates, especially in the state of dormant seeds. The reason for this increment could be problems in spindle function.
Keywords: mobile phones; electromagnetic waves; biological effects; mitosis; Lens culinaris Medik